(untitled) (Pulse, 2025)
Introduction: Blood transfusion is an integral part for managing transfusion dependent patients, surgical-gynecological emergencies and many other cases. Symmetry should be maintained between blood component requisition and utilization to ensure the optimization of blood transfusion service. Understanding the trend of proportion between demand and supply of blood component can set prediction for future. Optimum utilization of blood transfusion service will save time and laboratory resources. This study was conducted to evaluate the pattern of requesting and utilizing the blood components in a tertiary care hospital. Materials & method: It is a retrospective study. It was held in transfusion medicine and clinical hematology department of a tertiary care hospital from July to December 2024. Patient’s ID, blood request form and requested unit were kept under record. Simultaneously blood component units delivered for transfusion and units returned or not transfused were also recorded. Data were analyzed for cross match transfusion ratio (CT ratio), transfusion index (TI) and transfusion probability calculation (%T). Result: Over the six-month period 4,903 units of blood components were crossmatched for 4,454 patients. A total of 3,711 units were transfused to 3,035 patients. In this study C:T ratio was found 1.31, transfusion probability (%T) was 68.19 and transfusion index (TI) was 0.82 overall six months period. Analysis of the result of our study signifies appropriate use of blood units. Conclusion: Blood transfusion is a life-saving procedure for those with a genuine medical need. So, its use should always be under monitoring to prevent misuse of this valuable resource. Various transfusion indices like C:T ratio, %T and TI can be used as standard tools for ensuring appropriate use of blood. Persistent improvement in good transfusion practice can be achieved by continuous surveillance. Pulse Vol.17, 2025 P: 15-18